2021 Guidelines for Purchasing and Using Commercial Natural Enemies and Biopesticides in North America: IN849/IPM-146, 02/2021 - Leppla, Norman; LeBeck, Lynn M. (EDIS, 2021)
This 14-page guide written by Lynn M. LeBeck and Norman C. Leppla and published by the UF/IFAS Entomology and Nematology Department provides assistance in selecting, purchasing and using commercially available natural enemies and biopesticides for managing accurately diagnosed pest problems.